Evaluation of two bioadsorbents for removing paracetamol from aqueous media - Flores Nardy Ribeiro, Araceli Verónica; Belisário, Marciela; Moretto Galazzi, Rodrigo; Cazoni Balthazar, Daniele; de Godoi Pereira, Madson; Nardy Ribeiro, Joselito (Electronic Journal of Biotechnology, 2011)
The frequent contamination of water resources with drugs comprises one the most important environmental problems. In order to avoid serious disturbances for aquatic life, efficient and economically viable procedures should be developed for removing common pollutants, as paracetamol. From these considerations, the present work evaluated the efficiency of sugar cane bagasse (SCB) and vegetable sponge (VS), two natural adsorbents commonly found in Brazil, for retaining paracetamol molecules dispersed in aqueous solutions. Thus, systems composed of glass columns and peristaltic pumps were optimized and, for pH, the best value was 7.0. After optimisation, adsorption isotherms were built and it was possible to calculate the MACF values for SCB (120.5 µg/g) and VS (37.5 µg/g). Additionally, real matrices of pretreated water, from a municipal plant for water catchment, were enriched with paracetamol at 5 µM and passed through glass columns packed with SCB, VS and activated carbon (AC). The results showed that SCB was more attractive than AC in terms of price and efficiency (60% against 45% adsorption, respectively), while VS was responsible for removing 40% of paracetamol dissolved in the enriched water samples. Thus, the proposed natural adsorbents can be classified as viable materials to remove paracetamol from water used for human consumption.